FONDASI KEILMUAN BIMBINGAN DAN KONSELING INDONESIA - Habsy, Bakhrudin All (STKIP Andi Matappa, 2017)
Guidance and Counseling Science is an independent science which is rooted in philosophy and religion. The development of Guidance and Counselling Studies of philosophy Counseling is supported by educational science, psychology, sociology, anthropology, cultural integration and mutually reinforcing between philosophy and basic scientific disciplines and delivers philosophy that underlies Guidance and Counseling disciplines. The support of science and technology, culture, and the atmosphere becomes the basis for the development of the theory and praxis of guidance and counseling. The development of guidance and counseling is no longer confined to the school setting, but to reach areas outside of education that give situation and shades on the efforts on the implementation of the development of the more sensitive, anticipatory, proactive, and responsive individuals to the needs and demands of the development of individuals and society.